Protocolo de vacinação utilizando vírus recombinantes expressando as proteínas SAG1, SAG2 e SAG3 de Toxoplasma gondii - Erica Araujo Mendes (2011)
In this study we evaluated the ability of recombinant adenoviruses (rAd) encoding the antigens SAG1, SAG2 and SAG3 from Toxoplasma gondii (AdSAG1, AdSAG2 and AdSAG3, respectively) to induce immune responses and protection against the parasite. C57BL/6 mice received two doses of AdSAG1, AdSAG2, AdSAG3 or a control adenovirus (AdCTRL). The production of anti-SAG specific antibodies, as well as activation of T cells able to recognize those antigens were evaluated after vaccination. Each rAd elicited production of IgG antibodies specific against the SAG that they encode. On the other hand, only AdSAG1 led to significant activation of IFN- producing T cells, which responded in vitro to a T. gondii antigen extract and to a T CD8+ epitope (TPTENFTL) identified in the sequence of SAG1 protein. Vaccinated animals were challenged with a cystogenic strain of T. gondii for evaluation of survival and parasite load in brains. Only AdSAG1-immunized groups showed significant survival and reduction in brain cyst numbers. In vaccination experiments performed with T CD8+ cell-deficient mice, it was demonstrated that activation of IFN- producing T CD8+ cells specific to SAG1 is one of the protection mechanisms induced by AdSAG1. In a similar approach, by vaccinating MyD88 and IL-12 deficient mice with AdSAG1, we identified innate immune mechanisms activated in vivo by that rAd, which are involved in the differentiation of anti-SAG1 specific T lymphocytes into IFN- secreting cells and that contribute to the immunogenicity and protective properties of AdSAG1. To enhance the level of protection obtained with the homologous vaccination protocol (two doses of rAd), we constructed recombinant modified vaccinia virus Ankara (rMVA) encoding SAG1 and SAG2 to be used as boost dose after prime immunization with rAds, in a heterologous vaccination protocol. Again, protection was observed only after vaccination with viral vectors encoding SAG1, with a tendency to enhanced survival levels in groups of animals vaccinated according to the heterologous protocol (AdSAG1 + MVASAG1) in comparison to those groups that received homologous vaccination (two AdSAG1 doses). As for the parasite load, it was observed a significant difference between the two vaccination protocols, with the heterologous protocol providing a higher amount of reduction in brain cyst numbers. Altogether, the results indicate that the use of recombinant viral vectors is a useful approach for the development of immunization protocols against T. gondii